Activated Graphene Nanoplatelets Decorated with Carbon Nitrides for Efficient Electrocatalytic Oxygen Reduction Reaction. Issue 12 (19th August 2021) - Selvarajan, Premkumar; Fawaz, Mohammed; Sathish, CI; Li, Mengyao; Chu, Dewei; Yu, Xiaojiang; Breesec, Mark B. H.; Yi, Jiabao; Vinu, Ajayan
Abstract : Designing a metal‐free and highly efficient electrocatalyst with large number of active sites and high stability for oxygen reduction reaction (ORR) holds great promise for the commercial production of low‐cost and stable fuel cells. Herein, a novel strategy of introducing both porosity and electrochemically active carbon nitride (CN) matrix in the graphene nanoplatelets (GNPs) through a simple integration of chemical activation and the polymerization of CN precursor is reported. The characterization results confirm the successful integration of the CN matrix and the formation of the porous network in the GNPs. The highly dispersed CN matrix in the GNPs offers not only a large number of electrochemically active sites but also enhances the interaction with the oxygen intermediates, while the GNPs significantly reduce the electron localization in the catalyst. Due to the combined effect of CN matrix, porosity, and the conductive graphene framework, the prepared electrocatalyst gives exceptional ORR activity with a current density of 5.1 mA cm −2 and a positive onset potential of 0.87 V, which also shows excellent stability and tolerance toward methanol. The strategy adopted here may open a platform to design a series of novel electrocatalysts with enhanced performance for ORR in fuel cells. Abstract : A novel strategy of introducing both porosity and electrochemically active carbon nitride matrix in the graphene nanoplatelets is proposed. This unique approach offers not only active sites but also enhances the interaction with the oxygen intermediates which promotes the easy flow of electrons, offering exceptional oxygen reduction reaction (ORR) activity without any conductive carbon support or noble metals.